Politics of the gift towards a convivial society - Adloff, Frank 1969- (Bristol University Press, 2023)
At the heart of capitalism lies the idea of 'homo economicus': an ever-rational human being motivated by self-interest which arguably leads societies to economic prosperity. Drawing on French sociologist Marcel Mauss' influential theory of 'the gift', Frank Adloff shatters this fallacy to show mutual trust is the only glue that holds societies together; people are giving beings and they can cooperate for the benefit of all when the logic of maximizing personal gain in capitalism is broken. Acknowledging the role of women, nature, and workers in the Global South in transforming society, this book proposes a politics of conviviality, (from the Latin con-vivere: living together) for global and environmental justice as an alternative to the pursuit of profit, growth, and consumption